Sports Medicine: Justs the Facts - O'Connor, Francis G. [et al.]; Published by Holland Publishing (McGraw-Hill Education Singapore, 2005)
Easy access to concise, authoritative answers on the comprehensive range of health issues sports clinicians confront. Perfect as a desk reference or quick review for certification exams, this manual gives readers quick solutions to diagnostic and treatment questions, an abundance of useful tables and charts, emergency-care procedures, plus incisive strategies for keeping athletes healthy.
Includes Index
Keywords: Sports medicine -- Handbooks